HUBUNGAN PENGALAMAN MEMBACA SASTRA DENGAN KETERAMPILAN MENULIS PUISI SISWA SMP - Hidayati, Adelia; Atmazaki, Atmazaki; Abdurahman, Abdurahman (Universitas Negeri Padang, 2016)
ABSTRACT This article aims to see the relationship between the experience of reading literary and writing poetry skill of seventh grade students in SMP Negeri 3 Padang. The data of the research were the score of the questionnaires about experience of reading literature and the score of writing poetry test of seventh grade students in SMP Negeri 3 Padang. The result showed that: first, the mean scores of the experience of reading literature students classified as LDCs which was 66.86. Second, the mean scores of the poetry writing skills of students classified as B which was 76.19. Third, the value of t observed was bigger than T table (7.89> 1.69) which means the research hypothesis was accepted. Finally, it can be concluded that there was significant relationship between literary reading experience and writing poetry skill of seventh grade students in SMP Negeri 3 Padang.Â Kata Kunci: hubungan, pengalaman, membaca sastra, menulis puisi